"Immune" Thrombocytopenia as Key Feature of a Novel ADA2 Deficiency Variant: Implication on Differential Diagnostics of ITP in Children. Issue 2 (March 2019) - Sundin, Mikael; Marits, Per; Nierkens, Stefan; Kolios, Antonios G.A.; Nilsson, Jakob
Abstract : Thrombocytopenia presenting during early childhood is most commonly diagnosed as immune/idiopathic thrombocytopenic purpura (ITP), where the antibody-mediated destruction of thrombocytes is often transient. If treatment is indicated, the majority of patients respond to immune-modulation by intravenous immunoglobulin G infusion or systemic corticosteroids. Differential diagnoses to childhood ITP includes thrombocytopenia due to infections, drugs, rheumatologic conditions, immune dysregulation, and inherited bone marrow failures, for example, congenital amegakaryocytic thrombocytopenia. Isolated thrombocytopenia in an otherwise healthy appearing child that recurs after therapy and/or persists suggest a differential diagnosis rather than ITP. We present a case of symptomatic thrombocytopenia in a 2-year-old girl associated with adenosine deaminase deficiency.